Investigation of the Effects of Kitchen Hygiene Training on Reducing Personnel-Associated Microbial Contamination - Murat Doğan; Murat Ay (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2020)
Aim: In this study, it was aimed to determine the effect of kitchen hygiene training given to kitchen personnel in terms of reducing microbial contamination caused by personnel.Method: Before and after kitchen hygiene training, a total of 70 swap samples from the kitchen personnel hands was taken and examined microbiologically (S. aureus, E. coli and coliforms as pathogen bacteria indicator).Results: Before kitchen hygiene training, Escherichia coli (E. coli), coliforms and Staphylococcus aureus (S. aureus) strains developed on personnel hand surface samples. However, E. coli and coliforms did not develop on the samples after training and there was a 65% decrease in the count of S. aureus strains.Conclusion: It has been concluded that kitchen hygiene training has a positive effect on reducing microbial contamination caused by personnel.